1992
DOI: 10.1111/j.1467-1770.1992.tb01341.x
|View full text |Cite
|
Sign up to set email alerts
|

Affective Variables and a Less Commonly Taught Language: A Study in Beginning Japanese Classes*

Abstract: Learning a less commonly taught language or a “noncognate” language such as Japanese can be a daunting task for American students. The number of American students who are studying Asian languages at the university level‐in particular Japanese and Chinese‐is skyrocketing. Unfortunately, however, the attrition rate among these students is also very high. The present study explored the possible relationships between affective variables (e.g., attitudes, motivation, classroom personality) and students' linguistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
66
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 10 publications
14
66
1
Order By: Relevance
“…Apart from that, some studies showed that the level of anxiety increases when the students move to higher levels (Samimy & Tabuse 1992, Saito et al 1996. Samimy and Tabuse (1992) revealed that the level of anxiety among students increases as they move from one level to another.…”
Section: Foreign Language Anxiety and Level Of Studymentioning
confidence: 99%
“…Apart from that, some studies showed that the level of anxiety increases when the students move to higher levels (Samimy & Tabuse 1992, Saito et al 1996. Samimy and Tabuse (1992) revealed that the level of anxiety among students increases as they move from one level to another.…”
Section: Foreign Language Anxiety and Level Of Studymentioning
confidence: 99%
“…It should be noted that anxiety levels do not always naturally decrease as a function of time. Samimy and Tabuse (1992), for instance, reported a significant increase in the level of discomfort experienced within the Japanese classroom among 39 university students from the spring to the autumn quarter. Furthermore, in a recent study, Jee (2014) reported a significant increase in the scores of the full FLCAS and one of the FLCAS factors, that is, communication apprehension, from the first to the second semester among 12 Korean FL students.…”
Section: The Stability Of Fl Anxietymentioning
confidence: 99%
“…Saha (1983) says that the most important factor influences the result of study is the students' characteristic themselves. Samimy and Tabuse (1992) agree that affective variables such as attitude and motivation play a strong role in determining students' linguistic Langgeng Budianto performance in class. Oxford (in Shumim;1997) adds that the affective side of the learner is probably one of the most important influences on language learning success or failure.…”
Section: Introductionmentioning
confidence: 73%